Analisis Strategi Dinas Lingkungan Hidup Dalam Penanganan Sampah Liar di Kecamatan Johan Pahlawan - Vera Amalia Azmi; Darmawan Darmawan; Ernawati Ernawati; Susy Sriwahyuni; Kiswanto Kiswanto (KOLONI, 2026)
This study aims to analyze the strategy of the Environmental Agency (Environmental Service) of West Aceh Regency in addressing illegal dumping sites in Johan Pahlawan District based on Agus Dwiyanto's five dimensions of public organizational performance, namely productivity, service quality, responsiveness, responsibility, and accountability. This study employed a qualitative approach with a case study design. Eight informants were selected using purposive sampling, consisting of main informants, supporting informants, and key informants. Data were collected through in-depth interviews, observation, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. Data trustworthiness was ensured through source triangulation, technique triangulation, and data triangulation. The findings indicate that the Environmental Agency's strategy includes optimizing vehicle allocation and route distribution, scheduling operational activities, conducting patrols at illegal dumping hotspots, providing a WhatsApp-based complaint service, implementing standard operating procedures (SOP) for waste removal, enforcing the local Qanun through persuasive approaches and administrative responses, and applying digital reporting supported by before-and-after documentation. These strategies have improved the effectiveness of waste management services and enhanced environmental cleanliness at several illegal dumping sites. However, they have not fully prevented the recurrence of illegal dumping due to limited operational facilities, inconsistent law enforcement, and low public compliance. The study concludes that the effectiveness of illegal dumping management should be strengthened through hotspot-based monitoring, consistent enforcement of regulations, and increased participation of village governments and the community.